Implementation of the QFD Method to Identify Customer Needs - Ramadhani, Alfian; Widaningrum, Sri; Sutari, Wiyono (Jurnal Ilmiah Wahana Pendidikan, 2024)
Rumah BUMN (RB) is a facility provided to shape the digital economy ecosystem, one of which involves organizing training activities. Through regularly conducting training, RB Bandung needs to evaluate and improve its training activities. However, RB Bandung is not yet aware of the customer needs in these training activities. In this research, the Quality Function Deployment (QFD) method is utilized. This method is used to identify customer needs and articulate them into relevant technical requirements. After being identified using the QFD method, there are eleven customer needs: training with various issue focuses, training with experienced mentors, training that enhances participants' soft skills, training that enhances participants' capabilities, interactive training, training conducted according to schedule, training that can expand customer reach, training providing physical materials, training with various positive impacts, and training with confidently serving staff. Based on the normalized raw weight values, the first priority from customer needs is training with experienced mentors, with a normalized raw weight value of 0.12.